Pengaruh Model Pembelajaran Outdoor Study Terhadap Keterampilan Proses Sains Siswa Pada Pembelajaran IPA di Kelas IV Sekolah Dasar - Putri, Kurnia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to examine the effect of using the Outdoor Study learning model on students' science process skills in science learning at SDIT Nuruz Zaini, Langkat district, which is still relatively low. One factor in students' low science process skills is caused by the way teachers use the teaching and learning process, in teaching and learning activities teachers are less creative in using learning models/methods. Learning is essentially a process of interaction between teachers and students. This research is a Quasy Experimental research with a pre-test post-test Group Design type design. The population in this study was all class IV students, totaling 50 students. The research sample was 2 classes of class IV students at SDIT Nuruz Zaini, class IV A as the experimental class and class IV B as the control class and each class consisted of 25 students. The data collection technique used is a test instrument, namely pre-test and post-test question sheets consisting of indicators of science process skills. From the research results, there were significant results of science process skills after implementing the Outdoor Study learning model on plant parts and their functions, namely from an average pre-test score of 61.60, an increase in post-test score of 86.04. In this research, after being analyzed using the Independent simple t-test, it shows a Sig (2-tailed) value of 0.00 < 0.05, which means Ho is rejected. So it can be concluded that there is a significant influence of the Outdoor Study learning model on students' Science Process skills in science learning at SDIT Nuruz Zaini, Langkat Regency.